Monuments of History and the experience of World Heritage - reflections on the example of wooden sacral architecture - Andrzej, Siwek (Protection of Cultural Heritage, 2019)
The success and dynamic development of the World Heritage List shows the carrying capacity of the concept of identifying an elite group of goods important to the global community in terms of value. At the same time, the evolution of the list reveals threats of blurring of the message and compromising the value of entries after exceeding the critical quantitative mass. In the Polish context, one can see analogous processes and threats in relation to the group of the most valuable property - the Monuments of History. This raises questions about analogies and differences between the two sets of special assets and about the possibility of the Polish reception of the world’s concepts of protection. An excellent reference group showing system inconsistencies are Polish monuments of wooden sacral architecture. It is on this example that the concept of "Serial monuments of history" is being discussed. The connection of this concept with the obligation to develop management plans as an expression of an active protective attitude may contribute to the optimization of the system of protection of the property of the highest value. At the same time, comparative analyses included in the management plan methodology may become a tool for rationalizing new recognitions of monument of history, determining the limits of the phenomenon’s representation. Referring to a group of monuments, and not to a single, authoritatively appointed representative, is important both for the establishment of protection and education about heritage, as well as for the presentation of the cultural heritage of the country. There is no doubt that the collection of historical monuments and the subset of world heritage in the Polish system of monument protection should stand out as the most valuable assets, both in terms of prestige and due to the effectiveness and standards of protection specified in the management plans.